PD-L1 expression in neuroendocrine tumors of the lung - Tsuruoka, Kenjiro; Horinouchi, Hidehito; Goto, Yasushi; Kanda, Shintaro; Fujiwara, Yutaka; Nokihara, Hiroshi; Yamamoto, Noboru; Asakura, Keisuke; Nakagawa, Kazuo; Sakurai, Hiroyuki; Watanabe, Shun-ichi; Tsuta, Koji; et al. (Lung cancer (Amsterdam, Netherlands), 2017)
Various tumors express programmed cell death ligand 1 (PD-L1), an immune checkpoint ligand, the expression of which correlates with certain effects of anti-programmed cell death 1 (PD-1)/PD-L1 drugs. The aim of this study was to assess the frequency of PD-L1 expression in each of the types of neuroendocrine tumors of the lung. The subjects enrolled in this study were patients who had been diagnosed with neuroendocrine tumors of the lung and had been treated at the National Cancer Center Hospital (Tokyo, Japan) between 1982 and 2010. We performed immunohistochemical analysis on a tissue microarray (TMA) of the surgical specimens using the validated PD-L1 antibody clone, E1L3N. Tumor PD-L1 expression scores were calculated semiquantitatively (staining intensity [0–3]×stained area [0–100%]). A score of 1 was used as a cut-off to determine the presence or absence of PD-L1 expression. Among the 227 patients included in this study, the patient demographics were as follows: median age (range), 65 years (19–84); sex (male/female), 168/59; pStage (IA, IB, IIA, IIB, IIIA, IIIB, IV): 79, 36, 25, 29, 47, 6, 5, respectively; and histology was typical carcinoid (TC), atypical carcinoid (AC), large cell neuroendocrine carcinoma (LCNEC), small cell lung cancer (SCLC): 46, 6, 106, 69, respectively. The numbers (proportions) of PD-L1-expression tumors were as follows: TC/AC/LCNEC/SCLC, 0/0/11 (10.4%)/4 (5.8%). PD-L1 expression was apparent in 10.4% of LCNEC and 5.8% of SCLC tumors, and was not observed in carcinoid tumors.